Arabic Validation of the Pragmatic Language Skills Inventory to Assess Pragmatic Language Development in Preschoolers with and without Pragmatic Language Impairment - Ahmed Alduais; Fawaz Qasem; Hind Alfadda; Najla Alfadda; Lujain AlAmri (MDPI AG, 2022)
Objective: An individual's articulation of pragmatic language development (PLD) signifies successful social interaction with others. Therefore, it is important to detect early pragmatic language impairment (PLI), whether as a primary disorder or as a symptom of other neurodevelopmental disorders. This study reports on validating the Arabic version of the Pragmatic Language Skills Inventory (A-PLSI). Methods: The PLSI was subjected to various validation stages before the A-PLSI was created. To assess PLD in preschoolers with and without psychiatric histories, 264 preschoolers were assessed in several cities in Saudi Arabia by their teachers and speech-language pathologists. Results: The results of this study included three key findings. First, the established psychometric features, including construct validity, criterion-related validity, and (confirmatory) factor analysis, all reported a high level of measurability to consider the A-PLSI a valid instrument for assessing PLD in school settings and diagnosing PLI in clinical settings. Second, the A-PLSI provided empirical evidence by identifying children with and without PLI, documenting their progress on pragmatic language ability, and distinguishing between preschool children in school and clinical settings. In addition, the A-PLSI approved the typical norm that the older the children, the higher their level of PLD: the data showed higher performance for children aged 6-7 compared to the lower PLD level of children aged 4-5. Conclusion: The present study contributes to the existing literature on PLD assessment in a school setting and PLI diagnosis in a clinical setting. More importantly, it adds a new validated tool to the few available instruments in Arabic to assess PLD and diagnose PLI in Arabian contexts.